Pengaruh Matakuliah Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Biologi Universitasmuslim Buton - sanusi; Ridwan (Jurnal Sains dan Pendidikan Biologi, 2024)
The increase in the number of educated unemployed in Indonesia necessitates the need to increase the entrepreneurial interest of the younger generation. Increasing entrepreneurial interest requires the role of various parties, especially the role of government and universities. This research aims to determine the influence of entrepreneurship courses in increasing entrepreneurial interest in Biology Education students at Buton Muslim University. The population in the research were all students of the Faculty of Teacher Training and Education, Buton Muslim University, then the research sample was all Biology Education students, FKIP, Buton Muslim University. The research was carried out through several stages, namely preparation of research instruments, data collection and data analysis. The sampling technique used was Purposive Sampling Test. The research results showed that 52% of respondents agreed that entrepreneurship courses encourage students' entrepreneurial interest, 26% said they were neutral, and 22% said they strongly agreed.